The Concept of Cultural Tourism Development of Sanggraloka Sekar Wilis in Ponorogo with A Vernacular Architectural Approach - Eva Elviana; Erwin Djuni Winarto (Nusantara Science and Technology Proceedings, 2020)
Sanggraloka Sekar Wilis is a tourist spot developed by local people in the village of Kesugihan, Pulung sub-district, Ponorogo. By exploring the beauty of the natural panorama combined with the cool mountain air at the foot of Mount Wilis. Currently, the existing facilities reflect a family tour, but there are no facilities to accommodate cultural arts activities, which are so closely related to the people of Ponorogo. Therefore, it takes a development concept that combines tourist attractions, cultural attractions, and natural beauty. The development concept is manifested in the layout design (layout) and building layout designs that carry the theme of local-traditional architecture (vernacular). This research is included in the qualitative descriptive research category, which describes all the potentials and problems, and performs the qualitative analysis. To explore the culture of the people, the local art of the building (local architecture) and the character of the area were carried out using synchronic reading and diachronic reading techniques. So that the resulting formulation of the concept of cultural tourism development with a vernacular architectural approach. This research was conducted to raise the traditional values ??and localization of the art of building (vernacular architecture) in the concept of developing facilities to accommodate cultural arts attractions so that the appearance of the building is expected to reflect the locality. The results showed that using vernacular architecture can reflect the identity of the area, and can create harmony with the environment.